Rancang Bangun Sistem Informasi Akademik Berbasis Web (Studi Kasus SDIT AL USWAH) - Jaya, Megawati; Lusiani, Titik; Sutanto, Teguh (Jurnal JSIKA, 2012)
Academic information system is a web-based application that is designed and manufactured to process data related to academic information, including data of students, employees, Presence students, academic assessment, appraisal and qiroati Tahfidz, course schedule, the mandate of teaching, and assessment of student personality . Each member of the academic community have different access levels to different SIA. The level of access that is tailored to the needs and level of importance of each system user. SDIT AL uswah Surabaya is one unified Islamic elementary school that has problems ranging from frequent mistake inputting data, loss of data that has been collected, the data is not completed and the provision of information on the Presence of students, academic assessment, appraisal and qiroati Tahfidz, schedule of subjects, teaching mandate, and personality assessment of students who are not up to date. One good solution is to build a web-based academic information system to facilitate students and parents to determine a student´s academic information for teaching and learning as well as manage data well. The results obtained by using this system is to show students´ academic information online and up to date, Reducing errors in input data, and manage the data well and are less likely mistakes again. Keywords: Information Systems, Academic, web